Land-based marginal ice cliffs: Focus on Kilimanjaro - Winkler, Michael; Kaser, Georg; Cullen, Nicolas J.; Mölg, Thomas; Hardy, Douglas R.; Tad Pfeffer, W. (ERDKUNDE, 2010)
Land-based ice cliffs are intriguing features at the margins of glaciers around the world, but little is known about mechanisms of their formation and maintenance. A review on those ice cliffs, which are mostly associated with dry calving events, is presented. The focus is on the persistent, rarely-calving ice cliffs on the plateau glaciers of Kibo, the main peak of the Kilimanjaro massif (3°S, 37°E), Tanzania. Areal glacier shrinkage on Africa’s highest peak is closely linked to the recession of these ice cliffs and in order to extract climate change details from the plateau glaciers on Kilimanjaro, the sensitivity of the cliffs to climate fluctuations must be understood. Modelling solar irradiance, in conjunction with on-site measurements, revealed that direct insolation is the reason for (1) the predominant zonal alignment of the ice cliffs and (2) their bimodal annual recession. The former peculiarity occurs because near the equator steep north- and south-facing slopes receive only little solar energy, which prevents strong ablation. The bimodal recession pattern is caused by the particular annual path of the sun in the tropics, which either induces strong direct insolation on the Kilimanjaro ice cliffs from sunrise to sunset (“sunlit period”), or comparatively low (or no) direct insolation all day (“shaded period”). A 26 m high, 69° steep, and approximately south-facing sample cliff has been surveyed by terrestrial photogrammetry. The daily direct maximum insolation threshold between sunlit and shaded periods at the sample cliff is about 680 Wm-2. During the shaded period from March 4th to October 11th, where mean recession is only 1.4 cm/month, daily maximum insolation at the inclined sample cliff surface is below this threshold. During the sunlit period (mean recession rate 13 cm/month) daily insolation maxima exceed this threshold.